2018
DOI: 10.1016/j.scitotenv.2018.01.153
|View full text |Cite
|
Sign up to set email alerts
|

Plankton dynamics across the freshwater, transitional and marine research sites of the LTER-Italy Network. Patterns, fluctuations, drivers

Abstract: A first synoptic and trans-domain overview of plankton dynamics was conducted across the aquatic sites belonging to the Italian Long-Term Ecological Research Network (LTER-Italy). Based on published studies, checked and complemented with unpublished information, we investigated phytoplankton and zooplankton annual dynamics and long-term changes across domains: from the large subalpine lakes to mountain lakes and artificial lakes, from lagoons to marine coastal ecosystems. This study permitted identifying commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 120 publications
(131 reference statements)
2
34
0
Order By: Relevance
“…Such improvements in ecological forecasting should prove useful to environmental managers responsible for implementing measures aimed at mitigating adverse ecological effects of future changes in climate. Our findings highlight the importance of spatially distributed quantitative Long-Term Ecological Research in developing a predictive understanding of ecological responses to climate change in the world's oceans and they underpin the continued need for long-term research within the global and the national LTER networks, as already suggested in similar studies (Pugnetti et al 2013;Mirtl et al 2018;Morabito et al 2018). Last but not least, ILTER facilitate collaborations among scientific groups with different scientific topics and this study, catching the opportunity of the Special Issue proposed by the LTER-Italy network, demonstrates it.…”
Section: Discussionsupporting
confidence: 74%
“…Such improvements in ecological forecasting should prove useful to environmental managers responsible for implementing measures aimed at mitigating adverse ecological effects of future changes in climate. Our findings highlight the importance of spatially distributed quantitative Long-Term Ecological Research in developing a predictive understanding of ecological responses to climate change in the world's oceans and they underpin the continued need for long-term research within the global and the national LTER networks, as already suggested in similar studies (Pugnetti et al 2013;Mirtl et al 2018;Morabito et al 2018). Last but not least, ILTER facilitate collaborations among scientific groups with different scientific topics and this study, catching the opportunity of the Special Issue proposed by the LTER-Italy network, demonstrates it.…”
Section: Discussionsupporting
confidence: 74%
“…In bio-energetic models, zooplankton are categorized as a "source" [56], or pooled into a singular grouping [57] of the trophic level of 2 [58,59], without taking into account species-specific traits or differences in life stage. Because the relative biomass of zooplankton taxa can significantly change during a calendar year [60], and because trophic positions of taxa and their relationships are dynamic during the year, we can conclude that freshwater zooplankton cannot be clustered together in the same ecological compartment. We propose the inclusion of seasonality and the dynamic of species trophic roles of zooplankton in the construction of models predicting bio-magnification capability.…”
Section: Discussionmentioning
confidence: 97%
“…Samplings were taken weekly from January to December 2017 in the GoN, at the Long-Term Ecological-Research Station MareChiara (LTER-MC; 40°48.5′N, 14°15′E) [38, 39]. Environmental variables were measured as indicated in [40].…”
Section: Methodsmentioning
confidence: 99%